Respuesta :
Isolate y on both equations then equate
- x²-3x+2y=-4
- 2y=-x²+3x-4
- y=-x²/2+3/2x-2
Now you can equate it with second one to get x
Answer:
Substitute y = 3x + 2 into x² - 3x + 2y = -4
Step-by-step explanation:
Given system of equations:
[tex]\begin{cases}x^2-3x+2y=-4\\y=3x+2\end{cases}[/tex]
Since y is already isolated in the second equation, the best first step would be to substitute the second equation into the first equation, then solve for x.
Substitute equation 2 into equation 1:
[tex]\implies x^2-3x+2(3x+2)=-4[/tex]
Expand the brackets and simplify so that the equation equals zero:
[tex]\implies x^2-3x+6x+4=-4[/tex]
[tex]\implies x^2+3x+4+4=0[/tex]
[tex]\implies x^2+3x+8=0[/tex]
Now use the Quadratic Formula to solve for x.
Quadratic Formula
[tex]x=\dfrac{-b \pm \sqrt{b^2-4ac} }{2a}\quad\textsf{when }\:ax^2+bx+c=0[/tex]
Define the variables:
[tex]\implies a=1, \quad b=3, \quad c=8[/tex]
Substitute the values into the formula and solve for x:
[tex]\implies x=\dfrac{-3 \pm \sqrt{3^2-4(1)(8)}}{2(1)}[/tex]
[tex]\implies x=\dfrac{-3 \pm \sqrt{-23}}{2}[/tex]
[tex]\implies x=\dfrac{-3 \pm \sqrt{-1 \cdot 23}}{2}[/tex]
[tex]\implies x=\dfrac{-3 \pm \sqrt{-1}\sqrt{23}}{2}[/tex]
Remember that [tex]i^2=-1[/tex]
[tex]\implies x=\dfrac{-3 \pm i\sqrt{23}}{2}[/tex]
Therefore, the solutions to the system of equations are:
[tex]x=\dfrac{-3 + i\sqrt{23}}{2}, \quad \dfrac{-3 - i\sqrt{23}}{2}[/tex]
Learn more about systems of equations here:
https://brainly.com/question/27520807